1974
DOI: 10.1080/00380768.1974.10432607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic matter on the biodegradation of some organochlorine insecticides in submerged soils

Abstract: The effect of organic matter in the biodegradation of the organochlorine insecticides DDT, endrin, heptachlor, and the four isomers of BIIC (a, {3, r, and II) was studied In two soils under submerged soil condition. The four Insecticides were found to degrade biologically at a faster rate In non-sterilized than in sterilized soil. Adding organic matter to the soil seems to Increase its organic chemical adsorption of insecticides slightly, but not significantly when compared to Initial adsorption In the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 7 publications
1
15
0
1
Order By: Relevance
“…Cell growth was enhanced in both acclimated and unacclimated cultures, and low concentrations of glucose (0.1 mg l )1 ) stimulated dechlorination. Enhanced degradation of a-, b-, d-and c-HCH was observed in soil with low organic carbon content, when amended with 5000 mg kg )1 glucose under anaerobic conditions (Castro & Yoshida 1974). In another soil with higher organic carbon, the same application level of glucose inhibited HCH removal.…”
Section: Inorganic and Organic Amendmentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Cell growth was enhanced in both acclimated and unacclimated cultures, and low concentrations of glucose (0.1 mg l )1 ) stimulated dechlorination. Enhanced degradation of a-, b-, d-and c-HCH was observed in soil with low organic carbon content, when amended with 5000 mg kg )1 glucose under anaerobic conditions (Castro & Yoshida 1974). In another soil with higher organic carbon, the same application level of glucose inhibited HCH removal.…”
Section: Inorganic and Organic Amendmentsmentioning
confidence: 97%
“…Environmental factors affecting biodegradation of HCHs in pure cultures, soil microcosms and field plots HCH degradation under different redox conditions HCH biodegradation was initially thought to be an anaerobic process (Castro & Yoshida 1974;MacRae et al 1967MacRae et al , 1969MacRae et al , 1984Sethunathan et al 1983) and dechlorination of all four commonly found HCH isomers (a, b, d, c) has been observed under anoxic conditions in soil microcosms (Jagnow et al 1977;MacRae et al 1967), soil slurries (MacRae et al 1984Siddaramappa & Sethunathan 1975), field studies involving flooded soils (Chessells et al 1988), pure cultures (Jagnow et al 1977), and in situ in groundwater plumes contaminated with HCHs (Langenhoff et al 2002). Chessells et al (1988) reported a correlation between soil moisture content and removal rates of all four isomers in field agricultural soils treated with an HCH pesticide formulation.…”
Section: Physical Properties and Persistence Of Hchsmentioning
confidence: 99%
“…(Sahu et al 1992) and Bacillus brevis and Bacillus circulans (Gupta et al 2000) also degrade the four isomers of HCH. Also, earlier studies indicate that aerobic conditions are more favorable for HCH degradation as reported by Bachmann et al (1988) and Tu (1976) as compared to anaerobic conditions (MacRae et al 1967; Castro and Yoshida 1974). Bacterial strain Kocuria sp.…”
Section: Resultsmentioning
confidence: 76%
“…Repression of HCH biodegradation by glucose and other carbon amendments has been reported for aerobic soil slurries [2] and stirred anaerobic cultures [18]. However, other reports have indicated that carbon amendment might enhance HCH removal, depending on the nutrient requirements of the degrading microorganisms and the initial carbon content of the soil [9,12,17], or by promoting lower redox potentials and enhancing anaerobic degradation rates [26]. In this study, the extraction data demonstrated that HCH removal (without mineralization) was equal in treatments 4 and 6 by day 275 (Fig.…”
Section: Hch Degradation and Mineralization Of 14 C-c-hchmentioning
confidence: 99%